New insights in diagnostic laparoscopy - Berlet Maximilian; Hartwig Regine; Feussner Hubertus; Neumann Philipp-Alexander; Wilhelm Dirk (Current Directions in Biomedical Engineering, 2020)
The basic concept of Diagnostic Laparoscopy (DL) is old but not old-fashioned. – Before the rise of tomography and ultrasound there was just the direct look into the abdomen and onto the affected organ available. As open surgery comes along with trauma, blood loss and infection, every effort have been made to improve the access strategies. Finally, due to innovation in optics, video technology and computer science, the look into the abdomen through a “keyhole” is a standard procedure today. – In this review we give an overview of history, implications and cost-effectiveness of DL, attempting an extrapolation of its future role.